2020
DOI: 10.1080/20002297.2020.1807179
|View full text |Cite
|
Sign up to set email alerts
|

Oral mycobiome identification in atopic dermatitis, leukemia, and HIV patients – a systematic review

Abstract: Introduction: Oral mycobiome profiling is important to understand host-pathogen interactions that occur in various diseases. Invasive fungal infections are particularly relevant for patients who have received chemotherapy and for those who have HIV infection. In addition, changes in fungal microbiota are associated with the worsening of chronic conditions like atopic dermatitis (AD). This work aims, through a systematic review, to analyze the methods used in previous studies to identify oral fungi and their mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 110 publications
(273 reference statements)
1
12
0
Order By: Relevance
“…Candida species are present as part of the normal flora on the skin, and are common pathogenic yeasts causing mucocutaneous infections 32 . In previous culture‐based studies, higher frequencies of colonisation by C. albicans were found in the oral cavity and faeces of AD patients than in healthy controls 41–43 . In our review, the relative abundance of Candida did not significantly changed in AD lesions; however, some Candida species were only present in AD patients but not in healthy skin 14 .…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Candida species are present as part of the normal flora on the skin, and are common pathogenic yeasts causing mucocutaneous infections 32 . In previous culture‐based studies, higher frequencies of colonisation by C. albicans were found in the oral cavity and faeces of AD patients than in healthy controls 41–43 . In our review, the relative abundance of Candida did not significantly changed in AD lesions; however, some Candida species were only present in AD patients but not in healthy skin 14 .…”
Section: Discussionmentioning
confidence: 44%
“…C. albicans could also induce a delayed‐type hypersensitivity response on the skin by inducing the release of T cell co‐stimulatory molecules such as CD 207, CD 80 and CD86 46 . In evaluation of C. albicans ‐specific IgG levels, significantly lower levels of the yeast‐specific IgG were detected in AD patients, indicating the role of humoral immune response to Candida in the pathogenesis of AD 42 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, many studies have shown increased Candida colonization in HIV infection. [1,35,69,70] These studies support that HIV infection can significantly change the host oral microbiota. However, the effects of an altered oral microbiome on HIV-associated diseases remain to be shown.…”
Section: Salivamentioning
confidence: 90%
“…[31,33,34] In addition to bacterial communities, different fungi are also widely colonized in the human oral cavity. [35] It is known that in elderly and immunocompromised individuals, oral commensal fungi can also serve as opportunistic pathogens. Ghannoum et al [36] used internal transcribed spacer (ITS) sequencing to characterize the oral mycobiome in healthy individuals.…”
Section: The Human Oral Microbiomementioning
confidence: 99%
“…The human immunodeficiency virus (HIV) was initially identified in the 1980s in five young men affected by Pneumocystis carinii pneumonia and other opportunistic infections ( 1 ). HIV infection triggers an important immunosuppression condition by disrupting CD4+ T lymphocytes function, leading to a higher risk of developing opportunistic diseases ( 2 , 3 ), especially when CD4+ T cell count falls below than 200 cells/mm3, when the diagnosis of Acquired Immunodeficiency Syndrome (AIDS) is established ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%